Stereoselective synthesis of P-homochiral oligo(thymidine methanephosphonates). - Lesnikowski, Z J (1988)
An approach to the stereoselective synthesis of P-homochiral oligo(thymidine methanephosphonates) is described. Fully protected (Rp)- and (Sp)-diastereomers of MMTrTPMeTAC (3) were prepared in the stereospecific reaction of P-chiral nucleotide component 5'-O-monomethoxytritylthymidine 3'-O-[O-(4-nitrophenyl)methanephosphonate] (1) and 3'-O-acetylthmydine (2) bearing activated 5'-hydroxyl function. Deprotection of the 5'-OH group in 3 and subsequent stepwise reactions of activated 5'-OH oligonucleotide components with (Rp)- or (Sp)- isomers of 1 gave the trinucleotide MMTrTPMeTPMeTAC (4) and, subsequently, the tetranucleotide MMTrTPMeTPMeTPMeTAC (5) possessing all (Rp)- or all (Sp)- configurations at their internucleotide methanephosphonate P-atoms.